Causal association between metabolic syndrome and cholelithiasis: a Mendelian randomization study - Zhu, Qi; Xing, Yawei; Fu, Yunfeng; Chen, Xiaqin; Guan, Langyi; Liao, Foqiang; Zhou, Xiaodong (Frontiers in Endocrinology, 2023)
Background: Metabolic syndrome (MetS) has been associated with digestive system diseases, and recent observational studies have suggested an association between MetS and cholelithiasis. However, the causal relationship between them remains unclear. This study aimed to assess the causal effect of MetS on cholelithiasis using Mendelian randomization (MR) analysis. Methods: Single nucleotide polymorphisms (SNPs) of MetS and its components were extracted from the public genetic variation summary database. Inverse variance weighting (IVW) method weighted median method, and MR-Egger regression were used to evaluate the causal relationship. Sensitivity analysis was performed to ensure the stability of the results. Results: IVW showed that MetS increased the risk of cholelithiasis (OR=1.28, 95% CI=1.13-1.46, P=9.70E-05), and the weighted median method had the same result (OR=1.49, 95% CI=1.22-1.83, P=5.68E-05). In exploring the causal relationship between MetS components and cholelithiasis, waist circumference (WC) was significantly associated with cholelithiasis. IVW analysis (OR=1.48, 95% CI=1.34-1.65, P=1.15E-13), MR-Egger regression (OR=1.62, 95% CI=1.15-2.28, P=0.007), and weighted median (OR=1.73, 95% CI=1.47-2.04, P=1.62E-11) all found the same results. Conclusion: Our study indicated that MetS increases the incidence of cholelithiasis, especially in MetS patients with abdominal obesity. Control and treatment of MetS can effectively reduce the risk of gallstone formation.